Triggering a false alarm: wounding mimics prey capture in the carnivorous Venus flytrap (Dionaea muscipula) - Pavlovič, Andrej; Jakšová, Jana; Novák, Ondřej (New phytologist, 2017)
In the carnivorous plant Venus flytrap (Dionaea muscipula), the sequence of events after prey capture resembles the well-known plant defence signalling pathway in response to pathogen or herbivore attack. Here, we used wounding to mimic prey capture to show the similarities and differences between botanical carnivory and plant defence mechanisms. We monitored movement, electrical signalling, jasmonate accumulation and digestive enzyme secretion in local and distal (systemic) traps in response to prey capture, the mechanical stimulation of trigger hairs and wounding. The Venus flytrap cannot discriminate between wounding and mechanical trigger hair stimulation. Both induced the same action potentials, rapid trap closure, hermetic trap sealing, the accumulation of jasmonic acid (JA) and its isoleucine conjugate (JA-Ile), and the secretion of proteases (aspartic and cysteine proteases), phosphatases and type I chitinase. The jasmonate accumulation and enzyme secretion were confined to the local traps, to which the stimulus was applied, which correlates with the propagation of electrical signals and the absence of a systemic response in the Venus flytrap. In contrast to plant defence mechanisms, the absence of a systemic response in carnivorous plant may represent a resource-saving strategy. During prey capture, it could be quite expensive to produce digestive enzymes in the traps on the plant without prey.
Keywords: Droseraceae; chitinasy; Insecta; Animals; Enzymes; cyklopentany; Plant Proteins; Signal Transduction; rostlinné proteiny; enzymy; Cyclopentanes; Chitinases; Oxylipins; signální transdukce; zvířata; hmyz; oxylipiny